AB0697D CARDIOVASCULAR RISK FACTORS ARE HIGHER IN MALNOURISHED PATIENTS WITH SYSTEMIC SCLEROSIS. (June 2019) - Wojteczek, Anna; Ziętkiewicz, Marcin; Zdrojewski, Zbigniew; Małgorzewicz, Sylwia
Abstract : Background: Cardiovascular disease (CVD) is a well known complication in rheumatoid arthritis and systemic lupus erythematosus. Atherosclerosis (ATS) and its impact on CVD in patients with systemic sclerosis (SSc) still remains unclear. Most of studies are suggesting higher frequency of CVD in SSc in comparison to healthy controls. CVD is a leading cause of death in most developed countries, whereas in SSc population it ranges from 20 to 30%. The etiology of aTS in SSc is unknown. Traditional risk factors, endothelial dysfunction and inflammation can contribute to aTS in SSc population. However, there is lack of data about the impact of the nutritional status on CVD factors in SSc patients. Objectives: The aim of the study was to determine CVD factors among SSc patients depending on the nutritional status. Methods: In 55 patients with SSc (72, 7% well-nourished, 18, 1% malnourished, 9, 1% pre-cachexia) and 49 healthy controls we measured markers of endothelial dysfunction (asymmetric dimethylarginine - aDMA), inflammation (C-reactive protein - CRP, high sensitivity C-reactive protein - hsCRP, interleukin 6 - IL-6) and dyslipoproteinemia (oxidized low-density lipoprotein - ox-LDL, high-density lipoprotein- HDL, low-density lipoprotein – LDL and total cholesterol). Nutritional status was determined with subjective global assessment (SGA), body mass index (BMI), bioelectrical impedance analysis (BIA) and anthropometric measurements. Results: Well-nourished SSc patients had significantly higher level of IL-6 (6, 4±10, 1 vs. 2, 8±3, 6 pg/ml; p=0, 002) and lower HDL cholesterol (49, 9±11, 6 vs. 57±13, 6 mg/dl; p=0, 011) in comparison to healthy control. In malnourished SSc patients there was higher concentration of aDMA (1, 68±0, 53 vs. 1, 24±0, 34 µmol/l; p=0.003), CRP (18±28, 8 vs. 2, 4±2, 5 mg/l; p=0.04), IL-6 (21, 6±34, 9 vs. 2, 8±3, 6 pg/ml; p=0.004) and lower HDL cholesterol (42, 5±18, 3 vs. 57±13, 6 mg/dl; p=0.01) in comparison to healthy control. Pre-cachexia SSc group had significantly lower total cholesterol (166, 8±28, 5 vs. 219, 3±40, 9 mg/dl; p=0.008) and LDL cholesterol (96, 8±21, 6 vs. 139, 6±36 mg/dl; p=0.007). There were no differences in concentration of oxLDL and hsCRP in those groups. Conclusion: Nutritional status may play role in risk of CVD in SSc patients. Although its contribution to morbidity and mortality rates in CVD in SSc is yet to be established. Disclosure of interests: None declared